JSP practical guide for Java programmers - Brunner, Robert J. (Amsterdam ; Boston : Elsevier, 2003)
JavaServer Pages (JSP) is a technology for building dynamic web applications that can access databases and provide an interactive experience for users. It's a powerful technology with open source implementations (server and platform independent) for building enterprise Web applications. With JSP, existing business systems can be leveraged with minimal overhead, maintenance, and support. JSP: Practical Guide for Java Programmers is designed to cover the essentials of JSP including the basic JSP constructs and the relevant implicit objects as well as more advanced concepts such as incorporating JavaBeans, developing custom tags, utilizing the JSP expression language, building with the JSP Standard Tag Library, and developing complete JSP-Servlet application. Throughout the book, an electronic bank Web application is used to introduce new concepts, while demonstrating to the reader how the pieces fit together. *Covers the latest release of JSP, version 2.0, and covers new features such as the Expression Language and Standard Tag Library. *Includes a sample application of an electronic bank Web site, showing the power of JSP in providing the foundation for building Web applications . *Provides a clear, straight-to-the-point approach to the JSP so that readers can start using it in their own projects right away. *A supplemental web site includes code for all of the examples in the book as well as additional resources.
Chapter 1 Web Applications -- Chapter 2 Introduction to JSPs -- Chapter 3 JavaBeans and Forms -- Chapter 4 Custom Actions -- Chapter 5 Expression Language -- Chapter 6 Standard Actions -- Chapter 7 Build a Web Application.
Keywords: Java (Computer program language).; Electronic books